2011
DOI: 10.1093/ejo/cjq183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a fluoride-containing casein phosphopeptide-amorphous calcium phosphate complex on the shear bond strength of orthodontic brackets

Abstract: The purpose of this study was to investigate the effects of enamel pre-treatment with a new fluoride-containing casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) complex on the shear bond strength (SBS) of brackets bonded with etch-and-rinse or self-etching adhesive systems. The material comprised 66 extracted human premolars randomly divided into six equal groups with respect to the enamel pre-treatment and adhesive system employed: 1. No pre-treatment and brackets bonded with the etch-and-rinse adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 37 publications
2
26
3
Order By: Relevance
“…In addition, Park et al [24] reached a similar conclusion regardless of the adhesive system used for bond brackets on the teeth. Furthermore, Çehreli et al [25] reported that the application of CPP-ACPF before acid-etching has no effect on bracket SBS when using self-etching systems, but when applying its non-fluoride version CPP-ACP, significant decrease in bracket SBS was evident. Contradictory to our result, Kecik et al [28] observed that the application of CPP-ACP alone or combined with acidulated phosphate fluoride (APF) has shown significant increase in the SBS of orthodontic brackets.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Park et al [24] reached a similar conclusion regardless of the adhesive system used for bond brackets on the teeth. Furthermore, Çehreli et al [25] reported that the application of CPP-ACPF before acid-etching has no effect on bracket SBS when using self-etching systems, but when applying its non-fluoride version CPP-ACP, significant decrease in bracket SBS was evident. Contradictory to our result, Kecik et al [28] observed that the application of CPP-ACP alone or combined with acidulated phosphate fluoride (APF) has shown significant increase in the SBS of orthodontic brackets.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many authors have advocated CPP-ACP and CPP-ACP-F as the preventive agents for white spot lesions occurring during orthodontic treatment [19,20]. In present literature, many studies have evaluated the effect of CPP-ACP on the SBS of orthodontic brackets, but very limited studies are conducted to evaluate the effect of combination of these two agents on the SBS of orthodontic brackets [13,14,17,21]. So, this study was conducted to evaluate the effect of CPP-ACP and CPP-ACP-F on the SBS of orthodontic brackets bonded with two different adhesive systems.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of WSL treatment on the SBS of orthodontic brackets bonded to demineralized human enamel has been extensively investigated . The efficacy of such preventive methods should also be tested against the negative effects of WSLs on glass‐ceramic bonding.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of WSL treatment on the SBS of orthodontic brackets bonded to demineralized human enamel has been extensively investigated. 8,31,33,34 The efficacy of such preventive methods should also be tested against the negative effects of WSLs on glass-ceramic bonding. Within the limitations of this in vitro study, the null hypothesis was rejected because the demineralization-inhibiting methods affected the SBS of porce-lain discs bonded to demineralized enamel.…”
Section: Discussionmentioning
confidence: 99%